Industrial branding using digital media : case: The Switch - Lipiäinen, Heini (2012)
The shift from traditional marketing channels to the digital channels has been rapid which has generated new challenges and opportunities for business-to-business (B2B) communication and brand building processes. In general, studies of B2B branding are scarce, since branding has been approached as a business-to-consumer (B2C) function. In future B2B branding and brand management may well become a critical success factor in the market, since competition brought by globalization and market liberalization assisted by the internet revolution.